Urban regeneration, retail development and the role of information and communication technologies - Eunseong Jeong; Irene K. Shim; Mark I. Wilson (Netcom)
New urban planning concepts are progressive rather than radical perspectives from zoning to smart growth in the United States. In this respect, urban regeneration comes from adapting positive aspects from previous planning applications. The paper argues that urban regeneration pursues restoration of affirmative urban functions through appreciation of old and new perspectives. Today, information and communication technology (ICT) plays a significant role in urban planning, particularly for many small businesses that utilize ICT as a marketing tool. Urban retailing is one important element in urban regeneration due to its ability to create local employment. The paper empirically analyzes the features of local employment in San Francisco, Boston, and New York City to find evidence of urban regeneration through LQ and LQM.